CONFORMITY BEHIND THE SOCIAL AND SPATIAL SEGREGATION IN SUB-URBAN AREA A CASE AT GADING SERPONG NEW TOWN, TANGERANG - Mohammad Ischak; Bambang Setioko; Dedes Nurgandarum (TATALOKA, 2019)
The phenomenon of urban growth in rural areas created sub-urban areas like Tangerang region. Occupancy of space created by planned settlement against unplanned settlement raises spatial and social segregation. Previous studies have shown more on the negative side of the collision phenomenon with the point of view of the occurrence of physical and social unconformity between the newcomers as residents of planned settlements with the natives. On the other hand, it turns out that unplanned settlements still exist, thus raising the question of research is there conformity in the point of view of unplanned settlement settlers? To get an answer to the question, this research used analytical descriptive method, where data obtained directly from the field through observation and in-depth interviews with unplanned settlement settlers. The result of the analysis showed that although the spatial and social segregation is apparent, the community of unplanned settlers does not feel disturbed and the daily social economic activity of the community keeps going well, even the quality of life improves in some points. Such conditions create a form of internal conformity with parameters formulated by the community, including access to and from unplanned settlements, integrated infrastructures, open access to economic activities, and still guaranteed socio-cultural activities.